Affordances and Landscapes: Overcoming the Nature–Culture Dichotomy through Niche Construction Theory - Heras-Escribano, Manuel; De Pinedo-García, Manuel (Frontiers in Psychology, 2018)
In this paper we reject the nature-culture dichotomy by means of the idea of affordance or possibility for action, which has important implications for landscape theory. Our hypothesis is that, just as the idea of affordance can serve to overcome the subjective-objective dichotomy, the ideas of landscape and ecological niche, properly defined, would allow us to also transcend the nature-culture dichotomy. First, we introduce an overview of landscape theory, emphasizing processual landscape theory as the most suitable approach for satisfying both cultural and naturalist approaches. After that, we introduce the idea of affordance and we analyse a tension between sociocultural and transcultural affordances (affordances that depend on cultural conventions and affordances that depend on lawful information and bodily aspects of agents). This tension has various implications for landscape theory and ecological niches. Our proposal is that sociocultural and transcultural aspects of affordances could be systematically accommodated if we apply niche construction theory (the theory that explains the process by which organisms modify their selective environments) as a methodological framework for explaining the emergence of ecological niches. This approach will lead us to an integrative explanation of landscapes as the products of the interaction between human and environmental elements, making it a clear example of a concept that transcends the nature-culture dichotomy.